PELATIHAN PENULISAN OPINI UNTUK GURU BAHASA INDONESIA MA NU TASYWIQUTH THULLAB SALAFIYYAH KUDUS - Muhammad Noor Ahsin; Eko Widianto (InEJ: Indonesian Engagement Journal, 2021)
Writing opinions for teachers is very important. To improve the competence of teachers, it is necessary to write popular writing such as writing articles or opinions. Therefore, teachers in high school / MA equivalent schools are required to be able to create interactive learning media, including teachers at MA NU Tasywiquth Thullab Salafiyyah (TBS) Kudus. The problem is, not all teachers can write well. There are many Indonesian language teachers in the school. However, not many who have good writing skills. In other words there is still much to learn and practice writing directly. Based on interviews, Indonesian language teachers at MA NU TBS, writing for them is very important. Moreover, the demands of the 2013 curriculum. However, in these schools, teachers still have difficulty making good opinion writing. Based on this greeting, community service was carried out in the form of mentoring and training to write opinions for Indonesian language teachers at MA NU TBS Kudus. This community service is carried out using the asset based community development (ABCD) approach. This activity was carried out well. After training and mentoring the teacher's ability to write opinions becomes better. Other indicators of community coding are the results of the assisted subjects, most of whom stated that the teacher's writing ability was improved and the training was very useful.